Step
*
3
1
1
of Lemma
chinese-remainder2
1. r : ℤ
2. s : ℤ
3. a : ℤ
4. b : ℤ
5. g : ℕ
6. a1 : ℤ
7. a1 * g ∈ ℤ
8. b1 : ℤ
9. b1 * g ∈ ℤ
10. x : ℤ
11. y : ℤ
12. ((x * a1) + (y * b1)) = 1 ∈ ℤ
13. ¬(g = 0 ∈ ℤ)
14. x1 : ℤ
15. c : ℤ
16. (x1 - a) = ((a1 * g) * c) ∈ ℤ
17. c1 : ℤ
18. (x1 - b) = ((b1 * g) * c1) ∈ ℤ
⊢ g | (b - a)
BY
{ (With ⌜(a1 * c) - b1 * c1⌝ (D 0)⋅ THEN Auto')⋅ }
Latex:
Latex:
1.  r  :  \mBbbZ{}
2.  s  :  \mBbbZ{}
3.  a  :  \mBbbZ{}
4.  b  :  \mBbbZ{}
5.  g  :  \mBbbN{}
6.  a1  :  \mBbbZ{}
7.  a1  *  g  \mmember{}  \mBbbZ{}
8.  b1  :  \mBbbZ{}
9.  b1  *  g  \mmember{}  \mBbbZ{}
10.  x  :  \mBbbZ{}
11.  y  :  \mBbbZ{}
12.  ((x  *  a1)  +  (y  *  b1))  =  1
13.  \mneg{}(g  =  0)
14.  x1  :  \mBbbZ{}
15.  c  :  \mBbbZ{}
16.  (x1  -  a)  =  ((a1  *  g)  *  c)
17.  c1  :  \mBbbZ{}
18.  (x1  -  b)  =  ((b1  *  g)  *  c1)
\mvdash{}  g  |  (b  -  a)
By
Latex:
(With  \mkleeneopen{}(a1  *  c)  -  b1  *  c1\mkleeneclose{}  (D  0)\mcdot{}  THEN  Auto')\mcdot{}
Home
Index